PERAN GENDER DALAM PENINGKATAN KESEJAHTERAAN MASYARAKAT DESA WISATA COLO KABUPATEN KUDUS - Deny Aditya Puspasari; S Sariffuddin (TATALOKA, 2015)
Development of Village tourism development model is initiated by the Ministry of tourism and Creative Economy for poverty in rural paved. It's what makes Holy County Government initiative to develop the village into a tourist village Colo based nature tourism. Sunan Muria with fame in Kudus, making the village a Colo is located in the mountains of Muria as one of the tourist destinations that continues to evolve. See this potential, the villagers do tourism management in non-governmental and informal communities through the establishment of supporting tourism, such as taxi, hawkers and street vendors. There is a unique phenomena that are contained in the village of Colo namely management of tours with gender roles. Gender roles are not only happening in the improvement of well-being. Be interesting to examined how gender roles towards the improvement of the welfare of the Community tourism village Colo? to answer that question, this research uses a quantitative approach through descriptive statistics methods. Data were collected through document review, interviews and questionnaire to 134 KK as respondents. The results showed that gender roles related to the improvement of the welfare of the community. There is a pattern of increasing well-being of informally through changes in livelihood and ultimately increase revenue.